2016
DOI: 10.1128/aac.01421-16
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Novel Chikungunya Virus Protease Inhibitors

Abstract: dChikungunya virus (CHIKV; genus Alphavirus) is the causative agent of chikungunya fever. CHIKV replication can be inhibited by some broad-spectrum antiviral compounds; in contrast, there is very little information about compounds specifically inhibiting the enzymatic activities of CHIKV replication proteins. These proteins are translated in the form of a nonstructural (ns) P1234 polyprotein precursor from the CHIKV positive-strand RNA genome. Active forms of replicase enzymes are generated using the autoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 50 publications
(68 reference statements)
3
58
0
Order By: Relevance
“…To date, ribavirin is the only FDA-licensed drug tested in humans that effected a positive outcome in CHIKV-infected patients (167). High-throughput screening of chemical libraries (168)(169)(170)(171), as well as synthesis of designer drugs (172,173), has identified promising candidate CHIKV antivirals. Anti-CHIKV therapeutics also have been discovered or developed to directly target the viral replication cycle, including stages of entry, protein synthesis, genome replication, or enzymatic functions.…”
Section: Prospective Chikv Treatments and Vaccinesmentioning
confidence: 99%
“…To date, ribavirin is the only FDA-licensed drug tested in humans that effected a positive outcome in CHIKV-infected patients (167). High-throughput screening of chemical libraries (168)(169)(170)(171), as well as synthesis of designer drugs (172,173), has identified promising candidate CHIKV antivirals. Anti-CHIKV therapeutics also have been discovered or developed to directly target the viral replication cycle, including stages of entry, protein synthesis, genome replication, or enzymatic functions.…”
Section: Prospective Chikv Treatments and Vaccinesmentioning
confidence: 99%
“…To date, several studies have identified small-molecule inhibitors that inhibit CHIKV replication in cell culture (9)(10)(11)(12)(13)(14). Some nucleoside analogs, such as ribavirin, have also been shown to interfere with CHIKV replication.…”
mentioning
confidence: 99%
“…In this study, the most active compound had an IC 50 below 1 μM and molecular docking simulation suggested protease inhibition as a possible mode of action (Jadav et al 2015). Recently, for the first time, a new panel of predicted nsP2 inhibitors was shown to inhibit both the protease activity of nsP2 as well as CHIKV replication in cell culture (Das et al 2016). …”
Section: Interaction With Other Viral and Host Proteinsmentioning
confidence: 89%